Nutritional Status and Age at Menarche on Female Students of Junior High School - Rihul Husnul Juliyatmi; Lina Handayani (Institute of Advanced Engineering and Science, 2015)
Menarche is the first menstrual period in the middle of puberty. There are many factors that affect the age of menarche include nutritional status, genetic, environmental conditions, socioeconomic status, and education. The purpose of this research is to determine the relationship between nutritional status and age of menarche on female student of junior high school Ali Maksum Krapyak, Bantul, Yogyakarta. The research employed a cross sectional research design. The number of this sample was 81 female students that determined by total sampling. The statistical test used was Chi Square. The results of this research showed that there was a relationship between nutritional status and the age of menarche on female student of junior high school Ali Maksum Krapyak, Bantul, Yogyakarta (p value = 0.002) and the ratio prevalence was 3.077 (95% CI = 1.675 – 5.650); it means that respondents who have abnormal nutritional status get 3.007 times greater chance of experiencing abnormal menarche than respondents who have normal nutritional status.